Enhancement of Solubility and Bioavailability of Quercetin by Inclusion Complexation with the Cavity of Mono‐6‐deoxy‐6‐aminoethylamino‐β‐cyclodextrin. (24th July 2017) - Park, Kyeong Hui; Choi, Jae Min; Cho, Eunae; Jeong, Daham; Shinde, Vijay Vilas; Kim, Hyungsup; Choi, Youngjin; Jung, Seunho
Abstract : Quercetin (QUE) has a wide range of health benefits; however, its application is limited due to its low solubility. We synthesized mono‐6‐deoxy‐6‐aminoethylamino‐β‐cyclodextrin (Et‐β‐CD) to overcome this limitation. The solubility of QUE was increased 35.1‐fold compared with QUE, by its complexation with Et‐β‐CD. Changes in physicochemical properties following successful complexation were investigated using field emission scanning electron microscope, differential scanning calorimetry, and Fourier transform infrared spectroscopy. The complexation behavior of QUE and Et‐β‐CD in aqueous solution was monitored by 1 H nuclear magnetic resonance (NMR), 2D rotating frame nuclear overhauser, and diffusion‐ordered spectroscopy. The molecular docking simulation showed that the oblong shaped QUE is suitable for the formation of a stable complex with a characteristic cavity of Et‐β‐CD. Furthermore, the antioxidant activity and photostability of QUE was also improved after its complexation with Et‐β‐CD. From these results, we suggest that the characteristic elliptical cavity of Et‐β‐CD can be utilized for other hardly soluble drug molecules, which can expand the development of drug delivery systems. Abstract :